Bird Repellent Applied to Soybean Seed: Compatibility with Inoculant and Residuality in Cotyledons - Olivera, Lourdes; Rodríquez, Ethel; Ceretta, Sergio; Beyhaut, Elena (Agrociencia Uruguay, 2016)
Three species of doves cause significant economic losses in soybean (Glycine max [L.] Merr), for total or partial consumption of cotyledons during crop emergence. Repellents are a nonlethal alternative to reduce this damage, preventing birds from feeding on the crop. This study assessed the performance of seed-applied bird repellents. Tests involved repellents ability on reaching and staying in the cotyledons, and their effect on the survival of rhizobia on seed, nodulation and nitrogen fixation. We worked with Draza® (50 % methiocarb), Avipel® (50 % anthraquinone) and Rayén® (methyl anthranilate 30 %). Seeds were treated with the repellents and then inoculated with either liquid or peat-based formulations). The number of viable rhizobia on the seeds was measured two and seven days after treatment; and nodulation parameters and dry weight of aerial part in hothouse were determined. The content (ppm) of anthraquinone and methyl anthranilate in cotyledons was evaluated. The survival of rhizobia decreased whith methiocarb and anthraquinone but not with methyl anthranilate. Rhizobia nodulation ability and biological nitrogen fixation (BNF) were negatively affected by the use of methiocarb and anthraquinone, the latter being less harmful. Residuality of repellent on cotyledons was observed for anthraquinone but not for methyl anthranilate. Future research should be aimed at increasing the amount of methyl anthranilate present in cotyledons, without affecting the rhizobia.